Study of interlekin-4 (C-589T, rs2243250) gene polymorphism and interlekin-4 level in children with bronchial asthma - Shumna, T. Ye.; Titov, H.; Fedoseeva, O. S.; Lepetchenko, Ye. S.; Шумна, Таміла Євгенівна; Федосєєва, Олена Станіславівна; Лепетченко, Єлизавета Станіславівна (Stockholm : International Science Group, 2021)
The bronchial asthma (BA) is a heterogenic disease [1]. This disease has social significance because it leads to disability and death [2]. The bronchial asthma associated with a system of dysregulation of the immune system and the predominance of cells type Th-2 with increase in the secretion of cytokines, including anti-inflammatory interleukin-4 (IL-4). Interleukin-4 is encoded by the IL-4 gene, which is located on a specific site on chromosome 5q31 [3, 4]. The most significant today is the study of interleukin-4 gene polymorphism (C589T, rs2243250), when ytosine is replaced by thymine at position 589 of the cytoplasmic domain of the mature protein and is associated with allergic diseases. Therefore, the determination of the IL-4 gene polymorphism (C-589T, rs2243250) and the level of interleukin-4 in children makes it possible to predict the risk of development and the level of disease control [5]. Purpose. The study of polymorphism of the IL-4 gene (C-589T, rs2243250) and the level of the IL-4 cytokine in 89 children with bronchial asthma and in 25 children without allergic pathology.